A kind of imitation marble brick made of building solid waste and its preparation process

By using modified epoxy resin to cross-linking with glass fragments and modification of end-hydroxy-hyperbranched polyester, carbon fiber, boron nitride nanotubes in imitation marble bricks, its mechanical properties are improved, and the existing imitation marble bricks are solved. The problem of prone to cracks extends service life and reduces production costs.

CN117003549BActive Publication Date: 2025-01-14SHANXI XIZAI HIGH-TECH MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311039035.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-01-14
Estimated Expiration
2043-08-17

AI Technical Summary

Technical Problem

Existing imitation marble bricks produced using construction solid waste have poor mechanical properties and are prone to cracks, affecting their service life.

Method used

Use concrete pieces and sand as aggregates, combined with modified epoxy resin, glass fragments and silica, and the epoxy resin and glass fragments are fully cross-linked through the action of diethylene triamine to form a three-dimensional spatial network structure. Strengthen toughness and wear resistance, and improve the hardness and impact resistance of imitation marble bricks through end-hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotube modified epoxy resin.

Benefits of technology

It significantly improves the mechanical properties of imitation marble bricks, extends its service life, reduces production costs, and effectively reduces the generation of cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004400025910000051
    Figure BDA0004400025910000051
  • Figure BDA0004400025910000061
    Figure BDA0004400025910000061
  • Figure BDA0004400025910000071
    Figure BDA0004400025910000071
Patent Text Reader

Abstract

The present application relates to a kind of imitation marble brick made of building solid waste in the field of solid waste utilization technology and its preparation process. The imitation marble brick includes a blank and a glaze, and the raw materials for preparing the blank include the following components: 100-150 parts of building solid waste, 20-50 parts of modified epoxy resin, 6-10 parts of bis-(γ-triethoxysilylpropyl) tetrasulfide, 2-5 parts of diethylenetriamine, 4-9 parts of polyamide curing agent and 30-70 parts of water; building solid waste includes concrete fragments, sand and glass fragments; modified epoxy resin is an epoxy resin modified by terminal hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotubes. In this application, concrete fragments and sand are bonded by epoxy resin and play a major supporting role in the imitation marble brick; in addition, the main component of glass fragments is silicon dioxide, which is fully cross-linked with epoxy resin under the action of diethylenetriamine, improves the toughness and mechanical strength of epoxy resin, and thus improves the mechanical properties of imitation marble bricks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste utilization, and in particular to a construction solid waste imitation marble brick and a preparation process thereof. Background Art

[0002] Construction solid waste refers to the abandoned soil, materials and other waste generated by construction units in the process of new construction, renovation, reconstruction and demolition of various buildings, structures and pipelines, as well as by residents in the process of decorating and renovating their houses. Construction solid waste mainly includes soil, stones, concrete blocks, gravel, wood, metal materials, pipes, electrical appliances and other wastes.

[0003] At present, the main methods of treating construction solid waste are landfill, incineration and resource utilization. Among them, landfill and incineration will occupy a large amount of land resources and cause pollution to the atmosphere and soil environment. Therefore, resource utilization is a more environmentally friendly and sustainable way to treat construction solid waste.

[0004] Imitation marble bricks are ceramic bricks that imitate the pattern, color, texture, and appearance of marble, and are used as exterior wall bricks, interior wall bricks, floor tiles, etc. In the preparation of imitation marble bricks, high requirements are placed on the similarity of their appearance and mechanical properties. However, the mechanical properties of imitation marble bricks currently produced using construction solid waste are poor. Although the production cost is reduced, they are more prone to cracks than conventionally produced imitation marble bricks. Therefore, how to improve the mechanical properties of imitation marble bricks produced using construction solid waste is an urgent problem to be solved. Summary of the invention

[0005] In order to solve the problem that imitation marble bricks produced by using construction solid waste are prone to cracks, the present application provides a construction solid waste imitation marble brick and its preparation process. In the present application, concrete fragments are used as coarse aggregates and sand is used as fine aggregates, which are bonded by epoxy resin so that the two play a major supporting role inside the imitation marble brick; in addition, the main component of glass fragments is silicon dioxide, which can be fully cross-linked with epoxy resin under the action of diethylenetriamine, thereby improving the toughness and mechanical strength of epoxy resin, thereby improving the mechanical properties of the imitation marble brick, enabling it to withstand stronger external forces and prolonging its service life.

[0006] In the first aspect, the present application provides a construction solid waste imitation marble brick, which adopts the following technical solution:

[0007] A construction solid waste imitation marble brick, the imitation marble brick comprising a body and a glaze, wherein the raw materials for preparing the body comprise the following components by weight: 100-150 parts of construction solid waste, 20-50 parts of modified epoxy resin, 6-10 parts of bis-(γ-triethoxysilylpropyl) tetrasulfide, 2-5 parts of diethylenetriamine, 4-9 parts of polyamide curing agent and 30-70 parts of water;

[0008] The construction solid waste includes 30wt%-50wt% of concrete fragments, 45wt%-65wt% of sand and 5wt%-15wt% of glass fragments; the modified epoxy resin is an epoxy resin modified by terminal hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotubes.

[0009] By adopting the above technical solution, concrete fragments are used as coarse aggregate, sand is used as fine aggregate, and modified epoxy resin is used as adhesive to form a supporting skeleton of the imitation marble brick. In addition, the main component of glass fragments is silicon dioxide, and silicon dioxide and modified epoxy resin can be fully cross-linked under the action of diethylenetriamine, so that the three-dimensional network structure formed by the epoxy resin curing system contains a large number of Si-O bonds, which enhances the toughness and wear resistance of the modified epoxy resin, thereby improving the mechanical properties of the imitation marble brick.

[0010] The terminal hydroxy hyperbranched polyester contains a large amount of active terminal hydroxy groups, which can participate in the curing reaction of epoxy resin, and is connected with epoxy resin by chemical bond. Due to the presence of cavity in the terminal hydroxy hyperbranched polyester molecule, part of the energy can be absorbed when the imitation marble brick receives external force impact, which plays a buffering role, reduces the generation of cracks, and enhances the toughness of epoxy resin. And carbon fiber and boron nitride nanotubes have high strength and low friction coefficient, and the two are coordinated to modify epoxy resin to improve its mechanical strength and wear resistance, so the epoxy resin modified by terminal hydroxy hyperbranched polyester, carbon fiber and boron nitride nanotubes in this application has the characteristics of strong toughness, high strength and strong wear resistance. It is applied to the preparation of imitation marble brick, and the hardness, toughness and wear resistance of imitation marble brick can be improved, and the situation that imitation marble brick is prone to cracks can be improved.

[0011] The main raw materials for preparing the imitation marble bricks in the present application come from construction solid waste, which not only reasonably and effectively recycles the construction solid waste, but also reduces the production cost of the imitation marble bricks.

[0012] In the present application, the epoxy resin is bisphenol A epoxy resin purchased from Jinan Yanglan New Material Technology Co., Ltd.; the polyamide curing agent is polyamide curing agent 650 purchased from Suzhou Senfida Chemical Co., Ltd.

[0013] In some specific embodiments, the construction solid waste includes 40 wt % of concrete fragments, 50 wt % of sand and 10 wt % of glass fragments.

[0014] Preferably, the mass ratio of the modified epoxy resin to the glass fragments is (2-4):1.

[0015] By adopting the above technical solution, the mass ratio of the modified epoxy resin and the glass fragments is further adjusted, that is, the mass ratio of the modified epoxy resin and silica is adjusted, which helps to fully cross-link the silica and the modified epoxy resin and improve the mechanical properties of the imitation marble bricks.

[0016] In some preferred embodiments, the mass ratio of the modified epoxy resin to the glass fragments may be 2:1, 3:1, or 4:1, etc.

[0017] Preferably, the modified epoxy resin is prepared by the following preparation steps:

[0018] S1, adding epoxy resin, terminal hydroxyl hyperbranched polyester, hexahydrophthalic anhydride and 2-ethyl-4-methylimidazole into dimethylformamide solution and mixing them evenly to prepare a hyperbranched epoxy resin solution;

[0019] S2, adding carbon fiber, boron nitride nanotubes, disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate into water and mixing them evenly to prepare a pretreatment solution;

[0020] S3, after the hyperbranched epoxy resin solution and the pretreatment solution are uniformly mixed, dimethylformamide is removed to obtain a modified epoxy resin.

[0021] By adopting the above technical solution, there are tiny cavities in the terminal hydroxyl hyperbranched polyester molecules, and they can be connected to epoxy resin through chemical bonds. When the imitation marble brick is impacted by external force, it can absorb part of the energy and play a buffering role, thereby increasing the toughness and impact resistance of the imitation marble brick. Carbon fiber and boron nitride nanotubes have high strength and low friction coefficient. Modification of epoxy resin can enhance its mechanical strength and improve its wear resistance, thereby further improving the mechanical properties of imitation marble bricks.

[0022] Since carbon fiber and boron nitride nanotubes are entangled and agglomerated, disodium lauryl polyether sulfosuccinate is added. Disodium lauryl polyether sulfosuccinate can give carbon fiber and boron nitride nanotube surface charges, so that they repel each other and disperse in water. Disodium lauryl polyether sulfosuccinate can also improve the wetting properties of the carbon fiber and boron nitride nanotube surfaces, reduce the probability of adhesion and entanglement between carbon fibers and boron nitride nanotubes, and improve the dispersion of the two. The addition of sodium hexamethyl phosphate will increase the surface charge of carbon fiber and boron nitride nanotubes, enhance the repulsion between carbon fibers and boron nitride nanotubes, and the combination of the two can significantly improve the dispersion stability of carbon fiber and boron nitride nanotubes.

[0023] In some specific embodiments, the carbon fiber has a length of 3 mm and a diameter of 7 μm; the boron nitride nanotube has a length of 20 μm and a diameter of 30 nm.

[0024] Preferably, the mass of the terminal hydroxyl hyperbranched polyester is 3%-10% of the mass of the epoxy resin.

[0025] By adopting the above technical scheme, if the dosage of the terminal hydroxyl hyperbranched polyester is too much, it will affect the strength of the epoxy resin. If the dosage of the terminal hydroxyl hyperbranched polyester is too little, the toughness of the epoxy resin cannot be fully improved, and the buffering effect produced when the imitation marble brick is impacted by external force is weak. When the mass ratio of the two is controlled within the above range, the terminal hydroxyl hyperbranched polyester has a better improvement effect on the epoxy resin.

[0026] In some preferred embodiments, the mass of the terminal hydroxyl hyperbranched polyester is 5%, 7% or 9% of the mass of the epoxy resin.

[0027] Preferably, the total mass of the carbon fiber and the boron nitride nanotubes is 1%-5% of the mass of the epoxy resin, wherein the mass ratio of the carbon fiber to the boron nitride nanotubes is (2-5):1.

[0028] By adopting the above technical solution, the total amount of carbon fiber and boron nitride nanotubes is further adjusted. Excessive addition of the two will lead to a decrease in the glass transition temperature of the epoxy resin and a decrease in wear resistance; too little total addition of the two will result in no significant improvement in the strength and wear resistance of the epoxy resin. Excessive addition of boron nitride nanotubes will reduce the crosslinking density and curing degree of the epoxy resin. Therefore, controlling the mass ratio of carbon fiber and boron nitride nanotubes within the above range will help improve the mechanical strength of the epoxy resin.

[0029] In some preferred embodiments, the total mass of the carbon fiber and the boron nitride nanotubes is 3% of the mass of the epoxy resin, wherein the mass ratio of the carbon fiber to the boron nitride nanotubes may be 3:1, 4:1 or 5:1, etc.

[0030] Preferably, the mass ratio of the disodium lauryl polyether sulfosuccinate to sodium hexamethylphosphate is (1-4):1.

[0031] By adopting the above technical solution and adjusting the mass ratio of disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate, it is helpful to improve the dispersion stability of carbon fibers and boron nitride nanotubes, thereby improving the modification effect of epoxy resin.

[0032] In some preferred embodiments, the mass ratio of the disodium laureth sulfosuccinate to sodium hexamethylphosphate can be 2:1, 3:1 or 4:1, etc.

[0033] Preferably, the raw materials for preparing the green body further include 1-5 parts of N,N-dimethyl-p-toluidine.

[0034] By adopting the above technical scheme, the polyamide curing agent can improve the adhesion and toughness of the modified epoxy resin, but the curing speed is slow, which is prone to incomplete curing and affects the mechanical properties of the epoxy resin. N, N-dimethyl-p-toluidine can improve the curing speed of the polyamide curing agent. The combination of the two can improve the curing speed and curing effect of the epoxy resin, which is helpful to improve the mechanical properties of imitation marble tiles.

[0035] Preferably, the mass ratio of the polyamide curing agent to the N,N-dimethyl-p-toluidine is (1-3):1.

[0036] By adopting the above technical solution, the mass ratio of polyamide curing agent to N, N-dimethyl-p-toluidine is further adjusted, which helps to improve the curing speed and curing effect of epoxy resin, thereby improving the mechanical properties of imitation marble tiles. If the dosage of N, N-dimethyl-p-toluidine is too much, the imitation marble tiles will become too brittle.

[0037] In some preferred embodiments, the mass ratio of the polyamide curing agent to the N,N-dimethyl-p-toluidine can be 1.5:1, 2:1 or 3:1, etc.

[0038] In the second aspect, the present application provides a process for preparing imitation marble bricks from construction solid waste, using the following technical solution:

[0039] A process for preparing imitation marble bricks from construction solid waste, comprising the following steps:

[0040] T1. Crushing and screening the construction solid waste to obtain construction solid waste particles with a particle size of 0.02-2 mm;

[0041] T2, mixing the construction solid waste particles and bis-(γ-triethoxysilylpropyl) tetrasulfide evenly to obtain pretreated construction solid waste particles;

[0042] T3, mixing the pretreated construction solid waste particles, modified epoxy resin, diethylenetriamine and other raw materials, pouring them into a mold for curing and molding, and obtaining a green body after demolding;

[0043] T4, applying glaze on the surface of the green body and firing it to obtain imitation marble tiles.

[0044] In summary, the present application includes at least one of the following beneficial technical effects:

[0045] 1. This application mainly uses construction solid waste to prepare imitation marble bricks, which reduces the production cost of imitation marble bricks while making reasonable use of construction solid waste;

[0046] 2. The present application utilizes silicon dioxide in glass fragments to fully cross-link with epoxy resin, and a large number of Si-O bonds are added to the three-dimensional network structure in the epoxy resin curing system, thereby improving the toughness and wear resistance of the epoxy resin, thereby improving the mechanical properties of the imitation marble brick;

[0047] 3. The present application uses terminal hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotubes to modify epoxy resin, which can improve the toughness of epoxy resin and play a buffering role when the imitation marble brick is impacted by external force. On the other hand, it can improve the mechanical strength of epoxy resin, reduce the friction coefficient, and enhance the hardness and wear resistance of the imitation marble brick.

[0048] 4. The combination of disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate can give a large amount of negative charge to the surface of carbon fiber and boron nitride nanotubes, so that there is electrostatic repulsion between the carbon fiber and the boron nitride nanotubes, so that they can be stably dispersed in water, thereby improving the modification effect of the two on epoxy resin. DETAILED DESCRIPTION

[0049] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0050] Source of raw materials

[0051] Bis-(γ-triethoxysilylpropyl) tetrasulfide was purchased from Nanjing Xuanhao New Material Technology Co., Ltd.; terminal hydroxyl hyperbranched polyester was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0052] Preparation Example 1-3

[0053] The raw materials for preparing the modified epoxy resin in Preparation Examples 1-3 are shown in Table 1, wherein the mass ratio of carbon fiber to boron nitride nanotubes is 3:1, and the mass ratio of disodium lauryl polyether sulfosuccinate to sodium hexamethyl phosphate is 2:1. The modified epoxy resin is prepared by the following method: epoxy resin, terminal hydroxyl hyperbranched polyester, hexahydrophthalic anhydride and 2-ethyl-4-methylimidazole are added to a dimethylformamide solution and mixed uniformly to obtain a hyperbranched epoxy resin solution; carbon fiber, boron nitride nanotubes, disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate are added to water and mixed uniformly to obtain a pretreatment solution; after the hyperbranched epoxy resin solution and the pretreatment solution are mixed uniformly, they are concentrated by reduced pressure evaporation to remove dimethylformamide to obtain a modified epoxy resin.

[0054] Table 1. Raw materials for preparing modified epoxy resins in Preparation Examples 1-8

[0055]

[0056]

[0057] Preparation Example 4-5

[0058] The raw materials for preparing the epoxy resin in Preparation Example 4-5 are shown in Table 1. The difference between Preparation Example 4-5 and Preparation Example 2 is that the mass ratios of carbon fiber and boron nitride nanotubes are 4:1 and 5:1 respectively, and the rest are the same as Preparation Example 2.

[0059] Preparation Example 6-7

[0060] The raw materials for preparing the epoxy resin in Preparation Example 6-7 are shown in Table 1. The difference between Preparation Example 6-7 and Preparation Example 4 is that the mass ratios of disodium lauryl polyether sulfosuccinate and sodium hexamethylphosphate are 3:1 and 4:1 respectively, and the rest are the same as Preparation Example 4.

[0061] Preparation Example 8

[0062] The raw materials for preparing the epoxy resin in Preparation Example 8 are shown in Table 1. The difference between Preparation Example 8 and Preparation Example 4 is that the dosage of disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate is 0, and the rest is the same as Preparation Example 4.

[0063] Examples 1-3

[0064] In Examples 1-3, the imitation marble bricks include a body and a glaze, and the raw materials for preparing the body are shown in Table 2, wherein the modified epoxy resin is the modified epoxy resin prepared in Preparation Example 1, and the mass ratio of the modified epoxy resin to the glass fragments is 2:1. The imitation marble bricks are prepared by the following preparation process: firstly, the collected construction solid waste is crushed and screened, the concrete fragments are crushed into particles with a particle size of 2 mm, the sand is crushed into particles with a particle size of 0.3 mm, and the glass fragments are crushed into particles with a particle size of 0.05 mm to obtain construction solid waste particles; the construction solid waste particles are mixed evenly with bis-(γ-triethoxysilylpropyl) tetrasulfide to obtain pre-treated construction solid waste particles; the pre-treated construction solid waste particles, modified epoxy resin, diethylenetriamine, polyamide curing agent 650 and water are mixed evenly, poured into a mold, and demolded after curing and forming to obtain a body; glazing is applied on the surface of the body and fired in a kiln to obtain an imitation marble brick.

[0065] Table 2. Preparation of the green bodies of imitation marble tiles of Examples 1-5 Raw materials (kg)

[0066]

[0067] Embodiment 4-5

[0068] The raw materials for preparing the imitation marble brick bodies in Example 4-5 are shown in Table 2. The difference between Example 4-5 and Example 2 is that the mass ratios of the modified epoxy resin to the glass fragments are 3:1 and 4:1 respectively, and the rest are the same as Example 2.

[0069] Examples 6-12

[0070] The difference between Example 6-12 and Example 4 is that the modified epoxy resin is the modified epoxy resin prepared in Preparation Examples 2-8, and the rest is the same as Example 4.

[0071] Examples 13-15

[0072] The difference between Examples 13-15 and Example 10 is that N,N-dimethyl-p-toluidine is also added to the raw materials for preparing the imitation marble brick body, and the dosage of N,N-dimethyl-p-toluidine is 4kg, 3kg and 2kg respectively, that is, the mass ratio of polyamide curing agent to N,N-dimethyl-p-toluidine is 1.5:1, 2:1 and 3:1 respectively, and the rest is the same as Example 10.

[0073] Comparative Example 1

[0074] The difference between Comparative Example 1 and Example 1 is that an equal amount of epoxy resin is used in the raw materials for preparing the green body instead of the modified epoxy resin, and the rest is the same as Example 1.

[0075] Comparative Example 2

[0076] The difference between Comparative Example 2 and Example 4 is that in the raw materials for preparing the green body, the amount of concrete fragments in the construction solid waste is 53 kg, the amount of sand is 67 kg, the amount of glass fragments is 0 kg, and the rest is the same as Example 4.

[0077] Test Case

[0078] The imitation marble bricks prepared in Examples 1-15 and Comparative Examples 1-2 were tested for performance, including compressive strength and flexural strength, wherein the compressive strength and flexural strength were tested in accordance with GB / T 2542-2012 "Test Methods for Wall Bricks". The test results are shown in Table 3.

[0079] Table 3

[0080] Compressive strength(MPa) Flexural strength(MPa) Example 1 98.9 59.5 Example 2 107.6 63.4 Example 3 102.4 60.2 Example 4 112.8 65.9 Example 5 108.3. 62.8 Example 6 117.6 68.4 Example 7 114.5 66.2 Example 8 124.6 70.6 Example 9 118.1 67.7 Example 10 130.5 73.0 Embodiment 11 125.3 71.0 Example 12 90.7 48.3 Embodiment 13 132.0 74.3 Embodiment 14 136.9 76.2 Embodiment 15 133.4 74.9 Comparative Example 1 60.7 38.9 Comparative Example 2 72.1 43.6

[0081] According to the test results in Table 3, the imitation marble bricks prepared in Examples 1-15 and Comparative Examples 1-2 have a compressive strength of 60.7-136.9 MPa and a flexural strength of 38.9-76.2 MPa.

[0082] It can be seen from the test data of Examples 1-5 and Comparative Example 2 that the silicon dioxide in the glass fragments can undergo a cross-linking reaction with the modified epoxy resin to improve the toughness of the modified epoxy resin, thereby improving the mechanical properties of the imitation marble brick; when the mass ratio of the glass fragments to the modified epoxy resin is 1:3, the cross-linking reaction between the two is more sufficient, which can further improve the mechanical properties of the imitation marble brick.

[0083] It can be seen from the test data of Examples 4, 6-9 and Comparative Example 1 that after the epoxy resin is modified with terminal hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotubes, its toughness, mechanical strength and wear resistance are all improved, thereby improving the mechanical properties of the imitation marble brick. In particular, when the dosage of the terminal hydroxyl hyperbranched polyester is 7% of the mass of the epoxy resin and the mass ratio of the carbon fiber to the boron nitride nanotube is 4:1, the modification effect of the epoxy resin is more significant, the mechanical strength of the imitation marble brick is higher, and the probability of cracking is greatly reduced.

[0084] It can be seen from the test data of Examples 8 and 10-12 that in the modification process of epoxy resin, when the mass ratio of disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate is 3:1 respectively, the synergistic effect of the two is better, which can make carbon fibers and boron nitride nanotubes stably dispersed in water, help to improve the modification effect of epoxy resin, further improve the mechanical strength of epoxy resin, and reduce the friction coefficient of epoxy resin.

[0085] It can be seen from the test data of Examples 10 and 13-15 that adding N,N-dimethyl-p-toluidine to the raw materials for preparing the imitation marble brick body helps to improve the curing speed and curing effect of the modified epoxy resin, thereby improving the mechanical properties of the imitation marble brick, especially when the mass ratio of the polyamide curing agent to N,N-dimethyl-p-toluidine is 2:1, the curing speed and curing effect of the modified epoxy resin are better.

[0086] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A marble-like brick made from construction solid waste, characterized in that: The imitation marble brick comprises a body and a glaze, wherein the raw materials for preparing the body comprise the following components by weight: 100-150 parts of construction solid waste, 20-50 parts of modified epoxy resin, 6-10 parts of bis-(γ-triethoxysilylpropyl) tetrasulfide, 2-5 parts of diethylenetriamine, 4-9 parts of polyamide curing agent and 30-70 parts of water; The construction solid waste includes 30wt%-50wt% of concrete fragments, 45wt%-65wt% of sand and 5wt%-15wt% of glass fragments; The modified epoxy resin is an epoxy resin modified by terminal hydroxyl hyperbranched polyester, carbon fiber and boron nitride nanotubes; The modified epoxy resin is prepared by the following preparation steps: S1, adding epoxy resin, terminal hydroxyl hyperbranched polyester, hexahydrophthalic anhydride and 2-ethyl-4-methylimidazole into dimethylformamide solution and mixing them evenly to prepare a hyperbranched epoxy resin solution; S2, adding carbon fiber, boron nitride nanotubes, disodium lauryl polyether sulfosuccinate and sodium hexamethyl phosphate into water and mixing them evenly to prepare a pretreatment solution; S3, after the hyperbranched epoxy resin solution and the pretreatment solution are uniformly mixed, dimethylformamide is removed to obtain a modified epoxy resin; The mass of the terminal hydroxyl hyperbranched polyester is 3%-10% of the mass of the epoxy resin; The total mass of the carbon fiber and the boron nitride nanotubes is 1%-5% of the mass of the epoxy resin, wherein the mass ratio of the carbon fiber to the boron nitride nanotubes is (2-5):1; The mass ratio of the disodium lauryl polyether sulfosuccinate to sodium hexamethylphosphate is (1-4):

1.

2. The imitation marble brick made from construction solid waste according to claim 1, characterized in that: The mass ratio of the modified epoxy resin to the glass fragments is (2-4):

1.

3. The imitation marble brick made from construction solid waste according to claim 1 or 2, characterized in that: The raw materials for preparing the green body also include 1-5 parts of N,N-dimethyl-p-toluidine.

4. The imitation marble brick made from construction solid waste according to claim 3, characterized in that: The mass ratio of the polyamide curing agent to the N,N-dimethyl-p-toluidine is (1-3):

1.

5. A process for preparing imitation marble bricks from construction solid waste as claimed in any one of claims 1 to 4, characterized in that: The steps include: T1. Crushing and screening the construction solid waste to obtain construction solid waste particles with a particle size of 0.02-2 mm; T2, mixing the construction solid waste particles and bis-(γ-triethoxysilylpropyl) tetrasulfide evenly to obtain pretreated construction solid waste particles; T3, mixing the pretreated construction solid waste particles, modified epoxy resin, diethylenetriamine and other raw materials, pouring them into a mold for curing and molding, and obtaining a green body after demolding; T4, applying glaze on the surface of the green body and firing it to obtain imitation marble tiles.

Citation Information

Patent Citations

  • Terminal hydroxyl hyperbranched polyester toughened epoxy resin system and preparation method thereof

    CN109517342A

  • Epoxy reinforce composition for concrete construction

    KR1020040018090A

  • Artificial marble containing chips of plate-shaped waste glass and method for fabricating the same

    US20130116363A1